Stock price effects associated with changes in the composition of the Euro Stoxx 50 index - Liukko, Tuomas (My University, 2016)
Previous studies have documented abnormally high returns for stocks added to an index. Also stocks removed from an index have noticed to behave irrationally providing abnormally high negative returns during the index update. This price behavior is against the semi-strong form of market efficiency. The objective of this paper was therefore to study, if it is possible to create an investment strategy to benefit from this possible abnormal behavior also by using Euro Stoxx 50 index. The data consist of all the stocks added to and deleted from the index during 1999 until 2015. Both the short and long term price effects are measured for the additions and deletions separately. The first part of the paper consists of the theoretical part in which are presented the market efficiency, most common stock pricing models, and lastly the findings of the most important previous studies. The second part is the empirical part where the methodology and the results are presented. Market model is used to conduct an event study to measure the abnormal returns for both the added and deleted stocks during different time intervals. The cumulative abnormal returns are calculated for different periods around the announcement and the actual effective dates to better understand the possible explanations behind the abnormal returns. The results reveal that the markets may not be fully efficient around the index update and it can be possible to create an investment strategy to earn abnormal returns during the event window. The added stocks provide a statistically significant average abnormal return of 1,26% on the announcement date, and the returns increase further until the actual change day (CD), after which the returns reverse. The deleted stocks on the other hand have a statistically significant negative return of 1,8% on the CD-1 and the returns also reverse after the change day. The results support the price-pressure hypothesis. On long- term the portfolio consisting of the deleted stocks outperformed the index and the portfolio with added stocks.
Keywords: index composition change; abnormal returns; market efficiency; Euro Stoxx 50 index; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|